Les auteurs de vols à main armée à Montréal : une typologie empirique - Bellot, Sylvie (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1985)
This article presents a typology of armed robbers in Montreal, the result of a study of 39 authors of armed robbery. After a brief outline of the theoretical and methodological model used in this study, each type of armed robber is presented as follows : 1) the multireci-divist who is characterized by a large number of armed robberies, 2) the professional whose criminal activity is planned and organized, 3) the intensive robber who commits armed robberies for a very short period of time and 4) the occasional robber who commits very few armed robberies but many other crimes.